563. Tocilizumab in the Treatment of Critical COVID-19 Pneumonia. (31st December 2020) - Fisher, Matthew; Marcos, Luis; Monteforte, Melinda; Taub, Erin; Go, Roderick
Abstract: Background: The anti-interleukin-6 receptor monoclonal antibody tocilizumab has been proposed as a treatment for COVID-19 pneumonia although the efficacy remains unknown. Methods: Patients with COVID-19 confirmed by nasal swab PCR for SARS-CoV-2 who were admitted to Stony Brook University Hospital in Suffolk County, New York between March 10 th and April 2 nd and received tocilizumab while undergoing mechanical ventilation in any intensive care unit were retrospectively analyzed from data available in the electronic medical record. Baseline characteristics and clinical outcomes were compared to mechanically ventilated patients admitted during the same time period who received standard hospital protocol. Results: Forty-five patients received tocilizumab compared to seventy controls. Mean dose of tocilizumab given was 4.8mg/kg and mean time to receipt from initial intubation was 2.5 days. Baseline demographic characteristics, inflammatory markers, treatment with corticosteroids, and SOFA scores were similar between the two cohorts (Table 1). Patients who received tocilizumab had significantly lower Charlson co-morbidity index (2.0 versus 3.0, p = 0.01) and higher temperature (38.7 C versus 38.2 C, p = 0.004) than controls. There was no significant association between receipt of tocilizumab and the rate of extubation within fourteen days (44.4 percent versus 34.2 percent; OR = 1.53, 95% C.I. 0.71 – 3.30), discharge from hospital (51.1 percent versus 40.0 percent; OR = 1.568, 95% C.I. 0.737 – 3.337), or mortality (31.1 percent versus 41.4 percent; OR = 0.639, 95% C.I. 0.290 – 1.4407) (Table 2). Patients who were administered tocilizumab within two days of intubation had increased likelihood of extubation within fourteen days compared to those who were treated later (OR = 3.50, 95% C.I. 1.01 – 12.18). There was no observed increased risk of secondary infection in patients given tocilizumab (28.9 versus 25.7, OR = 1.1736, 95% C.I. = 0.507 – 2.714). Table 1: Patient Demographics and Baseline Characteristics Table 2: Primary Outcomes Conclusion: Tocilizumab was not associated with a significant improvement in rate of extubation, hospital discharge, or reduction in mortality in this retrospective cohort study of mechanically ventilated patients with COVID-19 pneumonia. Further studies are needed to determine whether earlier treatment may result in improved outcomes. Disclosures: All Authors : No reported disclosures